Boosting SMEs Performance in Surabaya on Post Pandemic Era - Fanny Thalia Limas (universitas teuku umar, 2023)
Small and medium-sized enterprises (SMEs) are playing a major role in many country including Indonesia, the definition of SMEs under Law No.20 of 2008 are corps owned by individual or groups of people, and it’s defined by their assets and annual sales, cited from ilo.org Indonesia’s SMEs are reaching 816.000 in total, employing 97 percent of local workforce in Indonesia and contributing 27 percent of GDP and we can say that SMEs are the backbone of the economy in Indonesia. Despite the fact, many SMEs failed to sustain in this era of globalization and pandemic, cited from bbc.com there are around 30 million of SMEs were bankrupt and closed during pandemic, hence the researcher did some research to find what are the most important factors to make SMEs sustain in this era. This study is located in Surabaya considering Surabaya as the second largest and fastest trading city with a significant SMEs growth since 2008 and high economic maneuver. Multiple linear regression was used for this study with a total 53 samples using google form as the data collection platform. Findings that all factors such customer value, transformational leadership, innovation and online marketing are significantly related to business performance. This study will accelerate SMEs growth to support indonesia economyKeywords: SMEs, pandemic, business, performance, key factors